Inflammation‐based prognostic score is a useful predictor of postoperative outcome in patients with extrahepatic cholangiocarcinoma. Issue 3 (March 2013) - Oshiro, Yukio; Sasaki, Ryoko; Fukunaga, Kiyoshi; Kondo, Tadashi; Oda, Tatsuya; Takahashi, Hideto; Ohkohchi, Nobuhiro
Abstract Background/purpose Recent studies have revealed that the Glasgow prognostic score (GPS), an inflammation‐based prognostic score, is useful for predicting outcome in a variety of cancers. This study sought to investigate the significance of GPS for prognostication of patients who underwent surgery with extrahepatic cholangiocarcinoma. Methods We retrospectively analyzed a total of 62 patients who underwent resection for extrahepatic cholangiocarcinoma. We calculated the GPS as follows: patients with both an elevated C‐reactive protein (>10 mg/L) and hypoalbuminemia (<35 g/L) were allocated a score of 2; patients with one or none of these abnormalities were allocated a score of 1 or 0, respectively. Prognostic significance was analyzed by the log‐rank test and a Cox proportional hazards model. Results Overall survival rate was 25.5 % at 5 years for all 62 patients. Venous invasion (p = 0.01), pathological primary tumor category (p = 0.013), lymph node metastasis category (p < 0.001), TNM stage (p < 0.001), and GPS (p = 0.008) were significantly associated with survival by univariate analysis. A Cox model demonstrated that increased GPS was an independent predictive factor with poor prognosis. Conclusions The preoperative GPS is a useful predictor of postoperative outcome in patients with extrahepatic cholangiocarcinoma.